Art and Influence, Presence and Navigation in Southern African Forager Landscapes - Sam Challis; Andrew Skinner (Religions, 2021)
With earlier origins and a rebirth in the late 1990s, the New Animisms and the precipitate ‘ontological turn’ have now been in full swing since the mid-2000s. They make a valuable contribution to the interpretation of the rock arts of numerous societies, particularly in their finding that in animist societies, there is little distinction between nature and culture, religious belief and practicality, the sacred and the profane. In the process, a problem of perspective arises: the perspectives of such societies, and the analogical sources that illuminate them, diverge in more foundational terms from Western perspectives than is often accounted for. This is why archaeologists of religion need to be anthropologists of the wider world, to recognise where animistic and shamanistic ontologies are represented, and perhaps where there is reason to look closely at how religious systems are used to imply Cartesian separations of nature and culture, religious and mundane, human/person and animal/non-person, and where these dichotomies may obscure other forms of being-in-the-world. Inspired by Bird-David, Descola, Hallowell, Ingold, Vieiros de Castro, and Willerslev, and acting through the lens of navigation in a populated, enculturated, and multinatural world, this contribution locates southern African shamanic expressions of rock art within broader contexts of shamanisms that are animist.